Mycotoxin contamination in foods: anti-nutritional factors - Cardwell, K. F. (International Food Policy Research Institute, 1999)
Mycotoxins come under regulatory limits in foods and feeds because they are carcinogens. Nevertheless, in addition to tumorigenic properties, many mycotoxins are anti-nutritional factors causing unthrifty growth and development of young animals. In the developed world, human exposure, and particularly exposure of children, to dietary mycotoxins is virtually non-existent because of regulatory standards. In developing countries, monitoring and enforcement of standards is rare. People are being exposed to unsafe levels of various mycotoxins, often in mixtures, and the consequences in terms of public health burden have been ignored. This paper presents information on the health effects that have been attributed to mycotoxin exposure from medical research literature; data on existing mycotoxin levels in west and central Africa; and nutritional indicators on Béninoise children with co-incidental appearance of symptoms of mycotoxin exposure with the weaning of children onto solid foods. The International Institute of Tropical Agriculture, in its maize IPM project, has recognized mycotoxins as one of the most important constraints to the goal of fostering human health and well being through agriculture. An overview of various research and development activities is given.